2019
DOI: 10.2196/12042
|View full text |Cite
|
Sign up to set email alerts
|

Use of Technology-Based Tools to Support Adolescents and Young Adults With Chronic Disease: Systematic Review and Meta-Analysis

Abstract: Background With the large amount of material that is readily available on the internet, there are endless opportunities for electronic health–literate patients to obtain and learn new information. Although novel, a Web- or mobile-based program can be a powerful way to engage adolescents and young adults (AYAs). The ongoing engagement of AYAs with chronic disease is vital not only to empower them but also to ensure a smooth transition from pediatric to adult health care. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 61 publications
(190 reference statements)
1
31
0
Order By: Relevance
“…Furthermore, a substantial number of IMIs (8 out of 19) are older than ten years, presumably not representative to the mobile technology and platforms available today. Second, although we were able to include substantially more studies than prior reviews ( Low and Manias, 2019 ; Thabrew et al, 2018 ), single meta-analytic comparisons might be still underpowered to detect significant effects ( Cuijpers et al, 2014 ; Harrer et al, 2019 ; Hedges and Pigott, 2001 ) – which might be in addition (very) small for single-component interventions, but clinically relevant for patients nonetheless ( Domhardt et al, 2019 ). Third (and clinically most relevant), given the high strain and specific needs of youth with CC, it might be that this particular group of patients is not responsive to IMIs to the same extent than other patient populations ( Andersson et al, 2019 ; Bendig et al, 2018 ; Domhardt et al, 2020b ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a substantial number of IMIs (8 out of 19) are older than ten years, presumably not representative to the mobile technology and platforms available today. Second, although we were able to include substantially more studies than prior reviews ( Low and Manias, 2019 ; Thabrew et al, 2018 ), single meta-analytic comparisons might be still underpowered to detect significant effects ( Cuijpers et al, 2014 ; Harrer et al, 2019 ; Hedges and Pigott, 2001 ) – which might be in addition (very) small for single-component interventions, but clinically relevant for patients nonetheless ( Domhardt et al, 2019 ). Third (and clinically most relevant), given the high strain and specific needs of youth with CC, it might be that this particular group of patients is not responsive to IMIs to the same extent than other patient populations ( Andersson et al, 2019 ; Bendig et al, 2018 ; Domhardt et al, 2020b ).…”
Section: Discussionmentioning
confidence: 99%
“…Next to these efforts toward precision medicine ( Cohen and DeRubeis, 2018 ) and “ precision digital health ” ( Domhardt et al, accepted ), important future directions for forthcoming research are on how to best improve interventions and maximize treatment outcomes. At that, involving the patients` perspective into intervention development ( Geirhos et al, submitted ; Holmes et al, 2018 ; Low and Manias, 2019 ) and disentangling the active ingredients of interventions by means of component and mediation studies ( Domhardt et al, 2020c ) might be key avenues, to increase the potential benefits of digital health interventions for youth with CC and other underserved populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, mobile health apps are gaining popularity and more patients are supposed to use mobile technologies and informational websites to receive information about certain diseases and treatment opportunities [ 29 – 31 ]. It is also anticipated that a variety of new internet-based approaches will flood the market in the near future especially with adolescents and younger adults as the target group [ 32 ]. However, despite the fact that in our study not many CKD patients were using internet-based health care technologies, the majority of patients are willing to consider the use within a medical context of consultation or treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The few studies that have addressed this topic have yielded mixed findings [ 50 ], and published materials frequently describe the methods rather than yet being able to share actual study results [ 52 55 ]. Two very recent comprehensive reviews concluded that, although adolescents and young adults were receptive to the technology, efficacy data were lacking [ 51 , 56 ]. Given the potential (although not yet realized) benefit of technological advances, we review some of the relevant studies here.…”
Section: Interventions In Adherencementioning
confidence: 99%